Slipping away - Marx, Richard; Capitol Records (United States : Capitol Records, 1998)
Contains the single taken from the album Richard Marx Greatest Hits.
CD 1 : Slipping Away / (4:13).
Koleksi Khas Wiramanja.
Title from disc label.
Keywords: Songs, English